Предмет: Математика,
автор: Lockers
Ответы
Автор ответа:
2
√(6+x-x^2)*(1/(2x+5)-1/(x+4)) >= 0
{6+x-x^2>=0
{1/(2x+5)-1/(x+4)>=0
{(3-x)(x+2)>=0
{(x+1)/((2x+5)*(x+4))<=0
Для первой -2<=x<=3
При x>=-1 откуда (2x+5)(x+4)<0
Откуда (-4,-2.5) объединяя с первым, нет решений
При x<=-1 откуда (2x+5)(x+4)>0 откуда
(-oo;-4) U (-2.5;+oo) объединяя с первым (-oo;-4) U (-2.5,-1]
Объединяя [-2,3] с (-oo;-4) U (-2.5,1] откуда
Ответ [-2,-1] и x=3
{6+x-x^2>=0
{1/(2x+5)-1/(x+4)>=0
{(3-x)(x+2)>=0
{(x+1)/((2x+5)*(x+4))<=0
Для первой -2<=x<=3
При x>=-1 откуда (2x+5)(x+4)<0
Откуда (-4,-2.5) объединяя с первым, нет решений
При x<=-1 откуда (2x+5)(x+4)>0 откуда
(-oo;-4) U (-2.5;+oo) объединяя с первым (-oo;-4) U (-2.5,-1]
Объединяя [-2,3] с (-oo;-4) U (-2.5,1] откуда
Ответ [-2,-1] и x=3
Похожие вопросы
Предмет: Биология,
автор: diophaha04
Предмет: Физика,
автор: huzinakamila16
Предмет: Физика,
автор: chelik228lox
Предмет: Математика,
автор: Аноним
Предмет: Математика,
автор: maynataliya